EARLY MARRIAGE AGAINST SOCIAL ADAPTATION ABILITY WITH SOCIAL ADAPTATION THEORY APPROACH (Studied in the district of Tembelang regency of Jombang) - Ngainu Rosidah; Dwi Puji; . Muarrofah (STIKES Insan Cendekia Medika Jombang, 2012)
Ealry marriage in Indonesia is still a lot going on especially in the distantly places, an early marriage related to the traditionandculture oftoday'steendatingthat too free, sexual behaviorthat is notwell controlled, somarriageatan early agegenerallyoccurred due to accidental(Unwed pregnancy). Adolescent development stopped due to early marriage, besides due to immaturityofthe individualmake them difficult in making decisions, negotiatewithcouplesandfamilies.This causesan impact onsocial adaptation. The purpose of this research was to analyze the effect of an early marriage to the ability of individual’s social adaptation with the approach of social adaptation theory. The research type was correlation analytic with cross sectional design. The research population was woman/wife of early marriage in the district of tembelang regency of jombang a number of 41people, with the sample was a number of 37 people which were taken by simple random sampling. The independent variablewas an early marriage and the dependent variable was social adaptation. The instrumentused was questionnaire, data processing used by editing, coding, scoring and tabulatingand performed statistical tests used by spearman rho. The research results showed that’s of 37 respondent nearly half of early marriage aged 17-19 years had social adaptation of Maladaptive wasamounted 18 respondent (48,6%). The influence analysis of early marriage to the ability of an individual’s social adaptation used statistical test of Spearman’s rho with  0,05 resulted value of P 0,002 so <. This research can be concluded that there is an effect of early marriage to the ability ofan individual's socialadaptationwithsocialadaptationtheory approachin the district of tembelang regency of Jombang, because ofearly marriagecanhave a negative impact to individual’s social adaptation untilbecomemaladaptive.